THE HISTORICAL EVOLUTION AND INNOVATIVE DESIGN OF QIANG COSTUMES - WANG, Y.; KHYNEVYCH , R. (Art and Design, 2024)
Рurpose. This paper analyzes the evolution process and cultural connotation of Qiang costume form, discusses the application form of Qiang costume elements in modern clothing design, and provides a theoretical basis for the innovative design of national costumes. Methodology. The field research method, literature analysis method, and case study method are used to analyze the evolution process, cultural connotation, and design application of Qiang costumes. Results. By studying the development process and style design changes of the Qiang costumes, it is concluded that its unique cultural connotation and design characteristics are closely related to the social characteristics, production methods and religious beliefs of the Qiang people. It is the materialized expression of the Qiang people's world outlook and national psychology. It reveals the reasons for the change of the Qiang costume modelling and proposes the method of using ethnic elements in modern costume design. Scientific novelty. This paper studies the development process of Qiang costume shape from the perspective of design, history, ethnology and anthropology, and puts forward that Qiang costume is the materialized expression form of local people 's world outlook, values and aesthetics, and clarifies that the change of Qiang costume shape is influenced by religious culture and Han-Tibetan culture. Suggestions are made in the form of integration of national costume elements with modern clothing design. Practical significance. The Qiang costume has been fused with other ethnic cultures in the course of historical changes, which is both inherited and changed, which is very inspiring to modern costume design. Digging deeper into the cultural connotation and design language of Qiang costume, so that it can innovate the design method and explore the design carrier while inheriting the national culture, so as to provide reference for the creation of a costume design that can embody both the traditional Chinese culture and the sense of the times.